Agricultural activity in the kingdoms of northwest Arabia before Islam - Al-Otaibi, Saleh Deifullah (Journal of Humanities & Social Sciences, 2022)
Agricultural wealth is one of the most important economic components of the inhabitants of the Arabian Peninsula before Islam, and its agricultural products can be classified into three sections: the first: agricultural products with commercial returns, foremost of which are incense of all kinds of frankincense, myrrh and patience, and the second: agricultural products for self-sufficiency, and to meet the nutritional need. And the third: products with a social and cultural dimension for the inhabitants of the Arabian Peninsula, which appears to me that most agricultural products in northwest Arabia were of the second and third categories, and the palm represented the most important crops in northwest Arabia, where its fruits were used as a food ingredient. Important, as it provided raw materials for the manufacture of wood, and wicker, and they offered the fruits of their palms to their deities to be satisfied with them. As for the water sources, the focus was on benefiting from groundwater. Wells were widely digging in the northwest of the Arabian Peninsula, the most important of which were the Hadaj well in Tayma, and the Sisra well in Adomatu. Wells also spread in the kingdoms of Dadan, Lehyan, and the Nabataeans. The Arabs had great ingenuity in the method of extracting water, and the method of irrigation, and perhaps he benefited from the advanced countries in this field.